Effect of probiotic Lactobacillus casei Shirota strain on aflatoxin B1 level in aflatoxin-induced rats - Nasrabadi, Elham Nikbakht (2013)
Aflatoxin B1 (AFB1) is considered as the most toxic food contaminant with harmful impact on human and animal health produced by Aspergillus species of fungi namely Aspergillus flavus (A. flavus) and Aspergillus parasiticus (A. parasiticus). It is classified as group one carcinogen by the International Agency for Research on Cancer that is linked to the etiology of liver cancer. Intervention and intercession approaches concentrate on pre-and post-harvest measures to reduce AFB1 levels in crops or on the individual level to modulate bioactivation and excretion of AFB1 or reduce its bioavailability. Microorganisms, especially bacteria, have been studied for their potential to reduce the bioavailability of aflatoxins as well as other food contaminants. Among them, lactic acid bacteria are known to have the ability to reduce the bioavailability of aflatoxins in vitro. This research aims to investigate the effect of probiotic Lactobacillus casei Shirota strain (LcS) on AFB1 level in aflatoxin induced rats through the weight, liver and kidney function tests, and also AFB1 blood serum level based on two separate studies of acute and chronic aflatoxicosis. Finally a comparison was done to observe the effect of probiotic LcS supplementation in different duration in acute and chronic exposure to AFB1. To achieve this purpose, an experimental study was conducted, and a total of 48 animals were divided into two groups (n=24) to conduct two studies of acute and chronic aflatoxicosis. Animals in acute aflatoxicosis experiment were divided into three subgroups of Aa, Ba, and untreated control (n=6). Group Aa (n=9) received LcS (108 CFU) by oral gavage daily for 7 successive days, and group Ba (n=9) received medium which was normal saline (1 ml) daily for 7 successive days. Immediately after the fourth probiotic and medium dose, animals of both groups of Aa and Ba were induced with a single oral dose of AFB1 in amount of 1.5 mg/kg body weight. Animals of chronic aflatoxicosis study were divided into three subgroups of Ac, Bc, and untreated control group as well. Group Ac was given LcS (108 CFU) by oral gavage daily for 20 successive days, and group Bc received normal saline (1 ml) again daily for 20 successive days. Immediately after the fourth probiotic and medium dose and from the 4th day, rats of both groups of Ac, and Bc started to receive multiple oral dose of AFB1 in amount of 25 !g/kg body weight daily for 5 days per week over the next 2 weeks.Based on the analysis of rats' body weight in acute aflatoxicosis, a significant difference was found between control group with the other two groups dosed with AFB1 (groups Aa and Ba) in days 6 and 7 (p<0.05). However there was no significant difference between groups Aa and Ba, but the mean of rat's body weight was higher in the group Aa. On the other hand there was a significant difference between control group and groups Aa and Ba in terms of blood liver and kidney biomarkers in acute aflatoxicosis (p<0.05). However there was no significant difference between groups Aa and Ba, the mean values of these biomarkers (ALT, AST, CREA and UREA) were greater in the group Ba in comparison to group Aa. To investigate the effect of LcS on AFB1 absorption, blood serum level of AFB1 was measured in all groups and then compared together. As expected aflatoxin B1 was detected from all of the serum samples expect for untreated control blood serum samples. The mean of AFB1 blood serum level in the group Ba was higher than group Aa. In the chronic aflatoxicosis study different results were obtained. With regard to rats' body weight; there was a significant difference between group Bc and the other two groups (untreated control and group Ac). This significant difference was found from day 9 to the end of the chronic aflatoxicosis study. Analysis of blood liver enzymes in chronic aflatoxicosis study revealed that there was a significant difference between untreated control group with groups Ac and Bc. A significant difference was also found between group Ac and group Bc (p<0.05). With regards to the level of creatinin and uric acid, similarly to acute aflatoxicosis study, analysis indicated that there was a significant difference between untreated control animals and animals of groups groups Ac and Bc (p<0.05). However no significant difference was found between groups Ac and Bc. AFB1 was detected from rats serum sampels of groups Ac and Bc, but compared to the acute aflatoxicosis study, there was a significant difference between groups Ac and Bc (p<0.05). According to the results of this study it can be concluded that probiotic LcS supplementation could improve the adverse effect of AFB1 induction more effective and significantly in chronic aflatoxicosis study compared to the acute aflatoxicosis study. Therefore longer duration of probiotic LcS supplementation with more number of animals is suggested for future studies to confirm the ability of probiotic Lcs to reduce the bioavalibilty of AFB1 in vivo.